(untitled) (Journal Intellectual Sufism Research (JISR), 2019)
Every educational institution would want a conducive and peaceful atmosphere in the school environment within the scope of teaching and learning. This does not only apply to certain levels, but almost at various levels of elementary, junior high school, high school and the like. But in the school environment there is still intense conflict and violence, there are several types of conflict and violence in the educational environment which are examined using qualitative descriptive types with the theory of conflict and violence approach, including: Types without conflict, open conflict, surface conflict and conflict. The components of violence are structural violence and cultural violence. Preventive action that should be done is first to socialize the type of punishment for the perpetrators of violence, secondly to design or implement a polite school system.